Effectiveness of Pranic Healing in Treatment of Insomnia: Case Series - Lama, Nishant (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Insomnia is the subject of a public health concern as it has affected the quality of life of millions of people. It has found to adversely influence physical, mental and social health as well as professional life. Globally, 37% of the adult population experience insomnia. There are many pharmacological, non-pharmacological and complementary and alternative measures to treat insomnia. Pranic Healing, the growing complementary energy medicine in the health care realm developed by Master Choa Kok Sui was used to describe its effectiveness in the healing of Insomnia. Methods: Case series study was applied to present the findings of two Nepalese adults being treated with insomnia with Pranic Healing. In this modality of energy medicine, treatment was done by assessing, cleansing and energizing the state of aura and energy level in the different energy centers through the rhythmic hand movement. Results: Cases were suffering from insomnia for more than a month which led them into stress, fatigue, irritation, and inefficiency. Pranic Healing therapy found that the over-activation of their Basic and Solar Plexus chakras were the immediate cause of insomnia. Pranic healer cleansed, energized and balanced their chakras with vital life energy or Prana for two healing episodes. Even today, both of the cases were found to have deep nocturnal sleep with active and efficient life. Conclusions: Pranic Healing, complementary therapy is effective in healing insomnia and in promoting, maintaining and restoring the health of people. However, large and controlled studies can be done to further analyze the effectiveness of Pranic Healing by upcoming researchers. Keywords: Pranic Healing, Insomnia, Master Choa Kok Sui, Nepal